Markers of pathology in serum of rats after “mild” stress - Yuzkiv, Ya. (Journal of Education, Health and Sport, 2025)
Background. Stress occurs as a result of the action of a very large number of factors. "Mild" stress occurs with moderate action of a stress-inducing factor, however, repeated action of such a factor can cause a number of diseases: cardiovascular, neuro-endocrine, neurotrophic, metabolic. The aim of our work was to study the state of pathology under the influence of "mild" stress by such biochemical markers as casein hydrolysis, BAEE hydrolysis (benzoyl-arginine ethyl ether) and ascorbic acid Methods. “Mild” stress was induced in rats by holding the animals at −20 °C for 5 minutes. After 5 and 24 hours, blood serum was obtained and proteolysis activity (substrate casein, pH 7.6), BAEE-esterase activity (substrate benzoyl-arginine ethyl ether), and peroxidation activity (substrate ascorbic acid) were determined in it. Results. An increase in proteolysis activity was found already 5 hours after stress and an almost twofold increase after 24 hours. On the contrary, peroxidation activity decreases after 5 hours and returns to normal after 24 hours. BAEE-esterase activity does not change after “mild” stress. Conclusion. Activation of proteolysis in the blood serum of rats under conditions of "mild" stress was detected. The level of oxidative processes in the blood serum of rats under conditions of "mild" stress is briefly reduced.